MULTIDIMENSIONAL ANALYSIS OF ICT INTEGRATION IN SECONDARY MATHEMATICS TEACHING - Bouchama, Youssef; Zaki, Moncef (International Journal of Engineering Technologies and Management Research, 2018)
This research aims at studying the integration of ICT in mathematics teaching at the junior and high school levels. An experiment was conducted with a sample of 120 Moroccan teachers from Marrakech-Safi, Casablanca-Settat, Rabat-Salé-Kenitra and Fes-Meknes regions. The teachers responded to a questionnaire of 31 modalities, which deal with the knowledge of the institutional aspects of ICT integration in teaching, educational planning, as well as some didactic aspects in the context of ICT integration. The analysis of the answers was conducted following a multidimensional approach. Thus, thanks to a Factorial Analysis of Multiple Correspondence (FAMC), we were able to identify the most discriminating factors in the integration of ICT and their order of importance. The results of this analysis highlight two factorial axes cumulating an absolute inertia of 76%, respectively representing « Successes and failures of ICT integration in teaching mathematics » and « The success factors in ICT integration».